(3fGLj GdYdj(B: (3GdTGgO h GdTgjO(B/ s - Abdulaziz, Omar (3YeQ YHOGdYRjRs ((3OGFQI GdKbGaI hGdGYdGe, McheI GdTGQbI; s, 2001)
Al Aqsa Intifada and the meanings of sacrifice and redemption. Naji Al Ali: Witness and martyr, Documents and certificates. Author: Omar AbdulAziz.
Arabic
Keywords: Naji Al Ali (3fGLj GdYdjs; 1973-1993; DS114-128.2 History of Asia- (Palestine)- History; Occupied Palestine (3adSWjf GdeMJdI s